Depression and HIV disease progression: A Mini-review - Yousuf, Abdilahi; Mohd Arifin, Siti Roshaidai; Musa, Ramli; Md. Isa, Muhammad Lokman (Bentham Open, 2019)
Background: Depression is the most common mental disorder and a leading cause of disability, which commonly presents unexplained psychological and physical symptoms. Depression and HIV/AIDS are commonly comorbid. This review provides an insight into the effect of depression on disease progression among people living with HIV.